Significance of switching of the nucleos(t)ide analog used to treat Japanese patients with chronic hepatitis B virus infection from entecavir to tenofovir alafenamide fumarate. Issue 3 (9th December 2019) - Uchida, Yoshihito; Nakao, Masamitsu; Tsuji, Shohei; Uemura, Hayato; Kouyama, Jun‐ichi; Naiki, Kayoko; Motoya, Daisuke; Sugawara, Kayoko; Nakayama, Nobuaki; Imai, Yukinori; Tomiya, Tomoaki; Mochida, Satoshi
Abstract: The significance of switching of the nucleos(t)ide analog used to treat patients with hepatitis B virus (HBV) from entecavir (ETV) to tenofovir alafenamide fumarate (TAF) is uncertain. The subjects of this study were 159 patients with HBV who received treatment with ETV followed by TAF. Among these patients, serial changes in the HBV marker levels were monitored in 92 patients in whom the serum HBsAg levels were ≥100 IU/mL during the 48‐week period immediately before and after the switching. A questionnaire survey for medication compliance was performed in 127 patients. The serum HBsAg levels (log IU/mL) decreased by 0.041 during the ETV treatment period and by 0.068 during the TAF administration period. The degree of reduction was higher during the TAF administration period than during the ETV administration period in patients without cirrhosis ( P  = .030), patients with genotype B HBV ( P  = .014), and patients with undetectable serum HBcrAg ( P  = .038). Multivariate analysis revealed the HBV genotype (B vs C; odds ratio, 3.400; P  = .025) and serum aspartate aminotransferase level (every 1+; 1.111; P  = .015) at the time of switching as factors influencing the treatment efficacy. Thirty‐six patients (28%) responded that the number of days that they forgot to take the drug decreased after the drug switching, and 77 patients (61%) reported feeling satisfied with the drug switching. Switching of the nucleos(t)ide analog used from ETV to TAF may be useful in the treatment of patients with HBV infection, as it is associated with both a decrease in the serum HBsAg level and improvement of the medication compliance.